The Share of Foreigners in One's Occupation and Attitudes towards Foreigners - Marco Pecoraro; Didier Ruedin (University of Neuchâtel, Institute of Economic Research (IRENE), 2017)
This paper examines the relationship between attitudes towards foreigners and the share of foreigners at the occupational level. Using a question on equal opportunities for foreigners from the Swiss House-hold Panel, ordered probit regressions with standard controls show that: (a) there is a negative association between the share of foreigners in one's occupation and positive attitudes towards foreigners; (b) there is a positive association between the share of recently arrived foreigners and positives attitudes towards foreigners. This suggests that workers are at the same time wary of competition with foreigners, and welcome their contribution to overcome labour shortages. Adding the occupational unemployment rate to the model indicates that objective competition may be as relevant as perceptions of competition. Controlling for other occupational characteristics establishes that the associations in (a) and (b) are probably caused by sorting on job quality. All results are robust to the potential endogeneity of the share of foreigners at the occupational level.
Keywords: F22; J24; J61; 330; Immigration; attitudes towards foreigners; labour market; occupational classification; ethnic concentration; unemployment; instrumental variables